Pemberontakan Satsuma dan Puisi “Battotai” Karya Toyama Masakazu - Anggia Ariska (English Study Program, Faculty of Humanities, Universitas Andalas, Padang, 2021)
The Satsuma Rebellion is one of many historical events that have occurred in Japan. Japan is a country that has a very long history, known as a country that has gone through various ages, one of which is the Meiji era or known as the Meiji Restoration. In a work of poetry “Battotai” by Toyama Masakazu can be seen a battle called the “Satsuma rebellion.” In a poem that describes the brave troops of the government army against the enemy using the sword in the Meiji period/Meiji Restoration. The purpose of this writing is to find out and explore the history of Japan through a work of poetry “Battotai.” To reveal the history in the poem used descriptive qualitative research methods. The results of this study find that in the poem